Modern trends in the development of the Ukrainian stock market - Hrabchuk, Oksana; Грабчук, Оксана Миколаївна (Дніпровський державний аграрно-економічний університет, 2025)
The task of the study was to formalize current trends and problems of the development of the stock market of Ukraine. The study presents the significance of the stock market of Ukraine for the development of the national economy. A mathematical approximation of the trends in the dynamics of the main parameters of the stock market is presented. A list of internal and external factors influencing the development of the stock market and the mechanism of their implementation are characterized. Завданням дослідження було формалізувати сучасні тенденції та проблеми розвитку фондового ринку України. У дослідженні представлено значущість фондового ринку України для розвитку національної економіки. Наведено математичне наближення тенденцій динаміки основних параметрів фондового ринку. Охарактеризовано перелік внутрішніх та зовнішніх чинників впливу на розвиток фондового ринку та механізм їх реалізації
Сучасні тенденції розвитку фондового ринку України
Keywords: stock market; фондовий ринок; approximation of dynamics trends; апроксимація тенденцій динаміки; regulatory and legal support; нормативно-правове забезпечення; stock market entities; суб’єкти фондового ринку; trading volume; обсяг торгів; issue volume; обсяг емісії; domestic government bonds; облігації внутрішньої державної позики; stock market development problems; проблеми розвитку фондового ринку